Transfusion of Blood Components during Orthotopic Hepatic Transplantation - S. V. Zhuravel; N. K. Kuznetsova; A. V. Chzhao; V. Kh. Timerbayev (Общая реаниматология, 2007)
Objective: to define preoperative factors determining a need for intraoperative packed red cell transfusion and its impact of the frequency and pattern of postoperative complications during orthotopic hepatic transplantation (OHT).Subjects and methods. The study included 31 recipients undergoing cadaveric liver transplantation. Group 1 comprised patients who were given allogenic blood red cells in the intraoperative period; Group 2 consisted of 11 (36%) recipients in whom OHT was made without allogenic red blood transfusion.Results. The baseline levels of hemoglobin (Hb) and hematocrit (Ht) were significantly higher in Group 2 (95±18 g/l (28±5%) versus 111±16 g/l (33±4%) in Groups 1 and 2, respectively).Conclusion. It is shown that cadaveric liver transplantation may be performed, without using donor packed red cells and that the preoperative levels of Hb and Ht are the indicators of blood transfusion.